Find the equation of the circle with center (

h,

k) = (

0,

0) and radius

r =

The standard equation for a circle is (x -

h)

^{2} + (y -

k)

^{2} =

r^{2}__Plugging in our numbers, we get:__(x -

0)

^{2} + (y -

0)

^{2} =

^{2}**(x - 0)**^{2} + (y - 0)^{2} = 0__Determine the general form of the circle equation given center (h, k) = (0, 0) and radius r = :__Expanding the standard form, we get the general form of x

^{2} + y

^{2} - 2

hx - 2

ky +

h^{2} +

k^{2} -

r^{2} = 0

__Plugging in our values for h,k, and r, we get:__Expanding the standard form, we get the general form of x

^{2} + y

^{2} - 2(

0)x - 2(

0)y +

0^{2} +

0^{2} -

^{2} = 0

x

^{2} + y

^{2} = 0

Combining our constants, we have our general form of a circle equation below:

**x**^{2} + y^{2} = 0